2021
DOI: 10.1093/jmammal/gyaa126
|View full text |Cite
|
Sign up to set email alerts
|

A new species ofAkodonMeyen, 1833 (Rodentia: Cricetidae: Sigmodontinae) endemic from the Brazilian Cerrado

Abstract: Akodon is the second most diverse genus of sigmodontine rodents, comprising 40 extant species. Widely distributed through different environments of South America, the genus ranges from forested to open-vegetation areas, from semiarid to mesic regions, and from Andean altitudes to the lowlands of eastern Brazil. In Brazil, most species are from the Atlantic Forest, inhabiting lowland and montane habitats, with a few taxa also present in areas transitional with the Cerrado and Pantanal. Based on an integrative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…However, it is important to note that under the crown ages estimated for these genera by Maestri et al (2017), Akodon is the genus with the highest rate (0.45; Oligoryzomys: 0.31; and Thomasomys: 0.27). The rates of Akodon and Oligoryzomys get much closer (0.52 and 0.49 respectively), but also above that of Thomasomys (0.38) if crown ages estimated by Steppan and Schenk (2017) S5 for the former) are not as well understood as in Oligoryzomys (see generic accounts in Patton et al, 2015 and the recent discussions on species limits for Akodon and Thomasomys in Brandão et al, 2021 andPacheco, 2021 respectively). It is also relevant to note that in a study of the diversification of the whole sigmodontine subfamily, a MEDUSA analysis detected shifts to higher rates at the nodes leading to Akodon and Thomasomys, but not with Oligoryzomys (Parada et al, 2015).…”
Section: Timing and Rate Of The Diversification Of Oligoryzomysmentioning
confidence: 82%
See 2 more Smart Citations
“…However, it is important to note that under the crown ages estimated for these genera by Maestri et al (2017), Akodon is the genus with the highest rate (0.45; Oligoryzomys: 0.31; and Thomasomys: 0.27). The rates of Akodon and Oligoryzomys get much closer (0.52 and 0.49 respectively), but also above that of Thomasomys (0.38) if crown ages estimated by Steppan and Schenk (2017) S5 for the former) are not as well understood as in Oligoryzomys (see generic accounts in Patton et al, 2015 and the recent discussions on species limits for Akodon and Thomasomys in Brandão et al, 2021 andPacheco, 2021 respectively). It is also relevant to note that in a study of the diversification of the whole sigmodontine subfamily, a MEDUSA analysis detected shifts to higher rates at the nodes leading to Akodon and Thomasomys, but not with Oligoryzomys (Parada et al, 2015).…”
Section: Timing and Rate Of The Diversification Of Oligoryzomysmentioning
confidence: 82%
“…The rates of Akodon and Oligoryzomys get much closer (0.52 and 0.49 respectively), but also above that of Thomasomys (0.38) if crown ages estimated by Steppan and Schenk (2017) are used. Additionally, it is worth noting that species boundaries in Thomasomys and Akodon (in particular for the former) are not as well understood as in Oligoryzomys (see generic accounts in Patton et al, 2015 and the recent discussions on species limits for Akodon and Thomasomys in Brandão et al, 2021 and Ruelas & Pacheco, 2021 respectively). It is also relevant to note that in a study of the diversification of the whole sigmodontine subfamily, a MEDUSA analysis detected shifts to higher rates at the nodes leading to Akodon and Thomasomys , but not with Oligoryzomys (Parada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic identifications were based on morphological, karyological, and/or molecular data. Nomenclature and classification follow Voss and Jansa (2009) for the marsupials and Patton et al (2015) for the rodents, and also follow recently published arrangements and species descriptions (Nascimento et al, 2013;Bonvicino et al, 2014a;Hurtado and Pacheco, 2017;Weksler et al, 2017;Suárez-Villota et al, 2018;Silva et al, 2019;Brandão et al, 2021;Fegies et al, 2021).…”
Section: Data Collection and Sampling Effortmentioning
confidence: 85%
“…Inventories based on standardized sampling design and high capture effort, with the use of complementary sampling methodologies in poorly surveyed areas, are highly recommended [e.g., central and eastern Mato Grosso (Brandão et al, 2019); southeastern and western Goiás (Hannibal et al, 2021); central Minas Gerais and eastern Mato Grosso do Sul (Mendonça et al, 2018)], as shown here, to provide robust datasets and increased knowledge on species diversity and distribution in the biome. The collection of vouchers and tissue samples, as well as karyotype data from the surveyed small mammals, is the basis for the description of new taxa (e.g., Bonvicino et al, 2014a;Brandão et al, 2021). Indeed, improvements on the systematics of several genera have contributed with the high richness found in open habitats, as well the high β-diversity found across localities, as previously widely distributed taxa are currently represented by distinct restricted-range species [e.g., former concepts of Oligoryzomys fornesi Bonvicino, 2005, 2015); Oryzomys subflavus (Percequillo et al, 2008); Thrichomys apereoides (Nascimento et al, 2013); and Micoureus demerarae (Silva et al, 2019)].…”
Section: Discussionmentioning
confidence: 99%